Role of CT(Computed Tomography) in Head Injury - Khadka, Bibek; Deka, Prabin Kumar; Karki, Alina (Journal of Manmohan Memorial Institute of Health Sciences, 2016)
Background: Head injury is considered as a major health problem that is a frequent cause of death and disability and makes considerable demands on health services. CT remains essential for detecting lesions that require immediate neurosurgical intervention as well as those that require in-hospital observation and medical management.Objectives: To evaluate the computed tomography findings in patients sustaining head injury and to emphasize the importance of computed tomography scan in head injury.Methodology: The study was conducted for the period of one year .It comprised a total number of eighty patients presenting to the emergency room(ER) with head injury and were evaluated by CT scan of head using siemens somatom dual slice spiral CT machine.Results: the study showed overall male to female ratio as 2.6:1. Head injury was most common in 31-50years of age group. Road traffic accidents (RTA) was the commonest mode of injury seen in 65% of patients. Loss of consciousness followed by vomiting and seizures were the common clinical presentations in head trauma patients respectively. According to Glasgow coma scale( GCS), most of the patients (68.8%)sustained mild head injury( GCS13-15). Most common abnormal CT findings were skull fractures 39(48.8%), extradural hematoma 31 ( 38.8%), subdural hematoma 21(26.2%) ,contusions 21(26.2%), subarachnoid hemorrhage14 ( 17.5%) and pneumocephalous 13 (16.2%) respectively. Linear skull fracture was the commonest among all other skull fractures. Patients sustaining severe head injury were mostly due to RTA (77%). The highest mortality was seen in patients with severe head injury (GCS 3-8). 5% also had cervical spine injury.Conclusion: CT is the most comprehensive diagnostic modality for accurate localization of the site of injury in craniocerebral trauma. The early and timely diagnosis of the precise lesion by CT not only had the substantial impact over instituting appropriate treatment and timely surgical intervention but also helped in predicting the ultimate outcome.Journal of Manmohan Memorial Institute of Health Sciences Vol. 2 2016 p.45-52